The Effect Of Der, Company Size, And Roe On The Firm Value Of Manufacturing Companies In The Automotive Sub-Sector And Its Components - Faris Ramadhan; Putri Mauliza; Nolla Puspita Dewi; Khaira Rizfia Fachrudin (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The purpose of this study was to determine and analyze the effect of DER, company size, and ROE on the company value of Automotive Sub-Sector Manufacturing Companies and their Components both partially and simultaneously. The research methodology uses an associative descriptive approach that explains the influence between the independent variable and the dependent variable. The data analysis technique uses Eviews tools with a total research sample of 11 Automotive and Component Subsector Manufacturing Companies with 5 years of observation time. The results of the DER tcount value of -0.008287 with a significance value of 0.0001 <0.05 mean that DER has a negative and significant effect on PBV in automotive companies listed on the IDX. The tcount value of total assets is 4.526332 with a significance value of 0.0002 <0.05, meaning that total assets have a positive and significant effect on PBV in automotive companies listed on the IDX. The tcount value of ROE is -4.239893 with a significance value of 0.0004 <0.05, meaning that ROE has a negative and significant effect on PBV in automotive companies listed on the IDX. The F value is 0.436104 and the significance level is 15.89043. Judging from the significance value, the value is 0.000013 <0.05. This means that DER, total assets, and ROE simultaneously have a significant effect on PBV.